Study on grafting assay and field screening of grafted combinations of Solanum torvum with F1 hybrid 704 brinjal against bacterial wilt caused by Ralstonia solanaearum - Thunkeesan, N.; Arasakesary, S.J.; Sritharan, S.; Pakeerathan, K. (National Science and Technology Commission, 6th floor, Wing D, Sethsiripaya Stage II, Battaramulla, 2026)
Brinjal (Solanum melongena L.) is a major vegetable crop grown in Sri Lanka. Even though the brinjal is a hardy plant, Bacterial wilt, caused by Ralstonia solanacearum,is a major destructive disease affecting brinjal production in the region of dry zone of Sri Lanka. Bacterial wilt is characterized by rapid wilting, stunting and eventual plant death due to colonization and blockage of the xylem by the pathogen [1]. Upon the environmental conditions such as high soil moisture, warm temperature [25 °C -35 °C], and heavy, poorly-drained soils are favorable, brinjal yield loss can go up to 70% [2]. Management is difficult, because the causal agent persists in soil and water and can survive associated with weeds and plant debris [3]. Chemical control is unreliable as it is a xylem dwelling bacteria, therefore, screening of resistant sources would be the ideal solution. All the current brinjal breeding programs are focusing on developing eggplant varieties or hybrids possessing disease and pest resistance [3]. Grafting of promising hybrid varieties with resistant root stock can be a viable means to mitigate this destructive disease. Therefore, the primary objective of this research was to assess disease resistance of grafted hybrid brinjal variety with Solanum torvum as root stock.